The Complexities of Growing Up: A Study in Colonial Hybridity and Womanhood in TsitsiDangarembga‟s The Book of Not - A, Vinodkumar (International Journal of Psychosocial Rehabilitation, 2020)
The non-white, non-Western women in the post-colonial world have been greatly affected by the political, economic and cultural effects of colonialism. Postcolonial feminist theorists analyze why postcolonial theory fails to address issues of gender. They analyze why the women of colour are not adequately represented in feminist scholarship. Postcolonial feminists believe that both the colonial power and patriarchy join hands in oppressing women. They try to explode the myth that women are a universal group and the idea of global sisterhood. This issue is addressed by Chandra Talpade Mohanty, a principal theorist in this realm in her essay, ‘Under Western Eyes’. She is of the view that third world women are depicted by the Western feminists as victims of masculine control and traditional culture. Thus, they overlook the cultural difference and the historical context. Ethel Crowley accuses Western feminists of theoretical reductionism when it comes to third world women. Western feminists and feminists outside of the West hold many differences in terms of race and religion which are not given due acknowledgement in Western feminism. Such differences are often ignored or denied by main stream feminism.